2014
DOI: 10.1186/1745-6215-15-24
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioral therapy for insomnia in euthymic bipolar disorder: study protocol for a randomized controlled trial

Abstract: BackgroundPatients with bipolar disorder experience sleep disturbance, even in euthymic phases. Changes in sleep pattern are frequent signs of a new episode of (hypo)mania or depression. Cognitive behavioral therapy for insomnia (CBT-I) is an effective treatment for primary insomnia, but there are no published results on the effects of CBT-I in patients with bipolar disorder. In this randomized controlled trial, we wish to compare CBT-I and treatment as usual with treatment as usual alone to determine its effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 31 publications
(33 reference statements)
0
19
0
2
Order By: Relevance
“…The cut‐off scores used to operationalize current mental states and the rationale for their selection were based on those employed in a clinical intervention trial for sleep problems in BD . To briefly summarize, the goal was to maximize the specificity of episode identification (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cut‐off scores used to operationalize current mental states and the rationale for their selection were based on those employed in a clinical intervention trial for sleep problems in BD . To briefly summarize, the goal was to maximize the specificity of episode identification (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Several clinical studies have explored the sleep profiles of BD cases and identified a range of individual characteristics associated with the presence or absence of sleep problems. Also, a number of research studies have employed actigraphy or other objective measures to record sleep patterns and their associations with circadian or other systemic disturbances . In addition, exploring how sleep symptoms respond to the treatments prescribed for acute BD episodes, there is increasing interest in the adjunctive use of chronobiotics such as melatonin agonists and/or chronotherapeutics such as cognitive and behavioural therapies to specifically target sleep problems in BD cases .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, the first module comprised of modified IGT sessions that incorporated psycho‐education, CBT and RP elements and helped familiarize clients with group processes and master basic self‐regulations and self‐management techniques. We hypothesized that these initial sessions could enable individuals to develop a more stable mental state and also act as a ‘lead‐in’ period that could enhance motivation to attend the second module based on MBRP (Simon et al , ; Steinan et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…BP has a chronic and remitting nature characterised by periods of depression and periods of hypomania or mania in many patients (11).…”
Section: Introductionmentioning
confidence: 99%